Rotorcraft simulation fidelity improvements through augmented rotor inflow - Agarwal, D.; Lu, L.; Padfield, G.D.; White, M.D.; Cameron, N. (My University, 2021)
In rotorcraft research, the prediction of correct off-axis response using a simulation model is a challenging task, particularly for hover and low-speed flight. This can be attributed to the complex aeromechanical behavior exhibited by a rotorcraft, including the unsteady and hysteretic nature of the main rotor wake and its coupling with the fuselage and empennage in manoeuvring flight. A traditional approach to improve the off-axis response prediction is to include the manoeuvre wake distortion effect arising from the variation of the induced inflow through the rotor disc. Various approaches have been developed to deal with this phenomenon but usually demand prerequisites of high levels of expertise and profound aerodynamic knowledge. This paper presents a new and practical approach to capturing this wake distortion through an augmented rotor inflow model. The proposed model is integrated into a nonlinear simulation using the FLIGHTLAB environment. The response comparisons between the simulation and flight test in hover indicate the good quality of the proposed model. The results reported are part of ongoing research at Liverpool and its partner Institutions into rotorcraft simulation fidelity for predicting dynamic behaviour for operationally-relevant mission-task-elements.